2020
DOI: 10.1186/s13229-020-00391-w
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological intervention to restore connectivity deficits of neuronal networks derived from ASD patient iPSC with a TSC2 mutation

Abstract: Background Tuberous sclerosis complex (TSC) is a rare genetic multisystemic disorder resulting from autosomal dominant mutations in the TSC1 or TSC2 genes. It is characterised by hyperactivation of the mechanistic target of rapamycin complex 1 (mTORC1) pathway and has severe neurodevelopmental and neurological components including autism, intellectual disability and epilepsy. In human and rodent models, loss of the TSC proteins causes neuronal hyperexcitability and synaptic dysfunction, althoug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 53 publications
(86 reference statements)
4
43
0
1
Order By: Relevance
“…Recent research in a TSC2 knockout iPSC model confirms the altered excitatory/inhibitory imbalance as observed in animal models, which is attributed to an increase in GABAergic signaling at inhibitory synapses [147]. However, neuronal growth cone studies in neurons derived from iPSCs report TSC2 heterozygous knockouts to have normal mTOR signaling but abnormal axon extension and insensitivity to inhibitory axonal guidance cues suggesting mTOR downstream processes to be the culprit and not necessarily mTOR itself [148].…”
Section: Cell Models Of Mtoropathies 411 Tscmentioning
confidence: 90%
“…Recent research in a TSC2 knockout iPSC model confirms the altered excitatory/inhibitory imbalance as observed in animal models, which is attributed to an increase in GABAergic signaling at inhibitory synapses [147]. However, neuronal growth cone studies in neurons derived from iPSCs report TSC2 heterozygous knockouts to have normal mTOR signaling but abnormal axon extension and insensitivity to inhibitory axonal guidance cues suggesting mTOR downstream processes to be the culprit and not necessarily mTOR itself [148].…”
Section: Cell Models Of Mtoropathies 411 Tscmentioning
confidence: 90%
“…The first group is the studies that described the generation of patient-specific iPSC lines [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ] that carry genetic variants in genes associated with epilepsy, such as SCN1A , GNB5, LGI1, GRIN2A, KCNC1, or KCNA2 ( Figure 3 , Table S1 ) [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. The second group is the studies that assessed the effects of convulsant and anticonvulsant drugs on hiPSC-derived neurons and astrocytes ( Figure 4 , Table S1 ) [ 57 , 58 , 59 ]. Some of these studies used healthy human stem cells to either generate an in vitro disease model by genetically manipulating a gene of interest; or by assessing the effects of different compounds on chemically induced “epilepsy-like” phenotype on otherwise healthy neurons [ 57 , 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some of these studies used healthy human stem cells to either generate an in vitro disease model by genetically manipulating a gene of interest; or by assessing the effects of different compounds on chemically induced “epilepsy-like” phenotype on otherwise healthy neurons [ 57 , 58 , 59 , 60 ]. Others used the iPSCs derived from patients carrying a specific gene variance of interest ( Figure 4 ) [ 27 , 36 , 38 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ,…”
Section: Resultsmentioning
confidence: 99%
“…This reduced inhibition further causes the mTOR hyperactivity, altered protein synthesis, enhancement of proliferation. Also, a study by Alsaqati et al demonstrated the TSC disorder which they characterized by hyperactivation of the mTORC1 pathway using the iPSC from ASD patients [ 150 ]. Secondly, the mutations in the Fmr1 gene leads to FXS and associated to abnormalities in the mTOR-dependent protein synthesis.…”
Section: Circadian Dysfunction Mtor and Asdmentioning
confidence: 99%